2019
DOI: 10.1051/e3sconf/20199203008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of fabric evolution using bidirectional shear wave velocity measurements

Abstract: In order to characterise fabric evolution, continuous bidirectional shear wave velocity measurements are performed in vertical and horizontal directions (V&H) on triaxial soil specimens during shearing in which two horizontal piezo-electrics were mounted on samples using a new measurement technique. The specimens are prepared by wet tamping method and then subjected to strain-controlled compressional shearing under drained and undrained conditions. The shear wave velocities of all drained specimens initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Different studies have also demonstrated that soil behaves anisotropically even in the small-strain domain (Shirley and Hampton 1978;Bellotti et al 1996;Pennington et al 1997;Hoque et al 1998;Ng et al 2004;Ezaoui et al 2009;Gu et al 2015;Fakharian et al 2019). Moreover, there are some shreds of evidence D r a f t suggesting that the fabric becomes greatly anisotropic at the critical state (Nakakuki and Oda 1972;Masson and Martinez 2001;Li and Yu 2009;Yan and Zhang 2012).…”
Section: R a F Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Different studies have also demonstrated that soil behaves anisotropically even in the small-strain domain (Shirley and Hampton 1978;Bellotti et al 1996;Pennington et al 1997;Hoque et al 1998;Ng et al 2004;Ezaoui et al 2009;Gu et al 2015;Fakharian et al 2019). Moreover, there are some shreds of evidence D r a f t suggesting that the fabric becomes greatly anisotropic at the critical state (Nakakuki and Oda 1972;Masson and Martinez 2001;Li and Yu 2009;Yan and Zhang 2012).…”
Section: R a F Tmentioning
confidence: 98%
“…The first major peak method was used to determine the travel time. For more details on the employed method, signal interpretation, horizontal bender element mounting, etc., please refer to Fakharian et al (2019) and Kaviani-Hamedani et al (2021).…”
Section: Sample Preparation and Test Programmentioning
confidence: 99%
“…The specimens were prepared using either "moist tamping" (MT) or "water sedimentation" (WS) methods. For specimens that were accompanied by bidirectional bender elements, the on-sample horizontal bender housings for MT and WS specimens during sample preparation are located in a parking spot "bender capsule" and out of parking spot "pre-penetrated in soil", respectively (for more details, refer to [14], [17].…”
Section: Soil Properties and Specimens Preparationmentioning
confidence: 99%
“…Classical critical state theory assumes that the soil fabric at the critical state becomes isotropic [16]. Nonetheless, soil behaves anisotropically during shearing on account of the microscopic characteristics of soils [17], [18]. This anisotropic behavior is also understood to influence the soil behavior in small-strain domain [11], [17], [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation